Corporate Political Donations: Influences from Directors’ Networks - Lu, Louise Yi; Shailer, Gregory E.; Wilson, Mark W. 1949- (2016)
Motivated by contemporary debates concerning whether directors inappropriately deploy corporate funds for corporate political donations and the limited research into managerial influence on corporate political donations, we examine the impact of director influences from a network perspective. Using a sample of large listed Australian corporations and their political party donation activity during 2000–2007, we find that both the professional and non-professional networks of directors influence corporate political donations. We observe these influences in relation to donations at the federal and state levels, and with respect to the choice of recipient political parties.
Keywords: Corporate Governance; Director networks; Interlocking directors; Corporate political donations